2009
DOI: 10.1093/eurheartj/ehp073
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary infusion of bone marrow-derived selected CD34+CXCR4+ cells and non-selected mononuclear cells in patients with acute STEMI and reduced left ventricular ejection fraction: results of randomized, multicentre Myocardial Regeneration by Intracoronary Infusion of Selected Population of Stem Cells in Acute Myocardial Infarction (REGENT) Trial

Abstract: In patients with AMI and impaired LVEF, treatment with BM cells does not lead to a significant improvement of LVEF or volumes. There was however a trend in favour of cell therapy in patients with most severely impaired LVEF and longer delay between the symptoms and revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
285
4
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(309 citation statements)
references
References 24 publications
14
285
4
6
Order By: Relevance
“…Interestingly, the meta-analyses suggested a trend toward a reduction in recurrent MI (Martin-Rendon et al 2008) and in the REPAIR-AMI (Intracoronary Progenitor Cells in Acute Myocardial Infarction) trial of 204 patients, even reported a significant reduction in mortality, rehospitalisation for heart failure, and repeated revascularization (Assmus et al 2010;. Of note, the overall benefit demonstrated in the meta-analyses with regard to left ventricular function needs to be tempered by the results of 3 other trials (Lunde et al 2008;Meyer et al 2006;Tendera et al 2009), which showed either no benefit or an initial benefit that was not persistent beyond 6 months. In this regard, it has been suggested, that differences in cell isolation protocols may have an impact on the functional capacity of the cells in the REPAIR-AMI1 and ASTAMI (Autologous Stem Cell Transplantation in Acute Myocardial Infarction) trials and therefore may account for the conflicting results.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Interestingly, the meta-analyses suggested a trend toward a reduction in recurrent MI (Martin-Rendon et al 2008) and in the REPAIR-AMI (Intracoronary Progenitor Cells in Acute Myocardial Infarction) trial of 204 patients, even reported a significant reduction in mortality, rehospitalisation for heart failure, and repeated revascularization (Assmus et al 2010;. Of note, the overall benefit demonstrated in the meta-analyses with regard to left ventricular function needs to be tempered by the results of 3 other trials (Lunde et al 2008;Meyer et al 2006;Tendera et al 2009), which showed either no benefit or an initial benefit that was not persistent beyond 6 months. In this regard, it has been suggested, that differences in cell isolation protocols may have an impact on the functional capacity of the cells in the REPAIR-AMI1 and ASTAMI (Autologous Stem Cell Transplantation in Acute Myocardial Infarction) trials and therefore may account for the conflicting results.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…human and animal models, to varying degrees of success [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In animal models, these cellbased therapies have demonstrated effectiveness in reducing infarct size and ventricular dilatation, and improving myocardial function [24][25][26] .…”
Section: Figurementioning
confidence: 99%
“…Regeneration by Intracoronary Infusion of Selected Population of Stem Cells in Acute Myocardial Infarction (REGENT) trial", where Michał Tendera was the first author was cited 148 times [4]. The "Guidelines on the diagnosis and management of acute pulmonary embolism: the Task Force for the diagnosis and management of acute pulmonary embolism of the European Society of Cardiology (ESC)", were Adam Torbicki was an author was cited 580 times [5].…”
Section: Cd34(+)cxcr4(+) Cells and Non-selected Mononuclear Cells Inmentioning
confidence: 99%